The use of micronized progesterone in menopausal hormonal therapy in the light of the most recent study results - Paszkowski, Tomasz; Woźniakowska, Ewa; Wrona, Wojciech; Szkodziak, Piotr; Radomański, Tomasz (Menopause Review/Przegląd Menopauzalny, 2011)
Micronized progesterone (MP) can be used in the menopausal hormonal therapy (MHT). Micronized progesterone provides an effective endometrial protection during MHT. Hormonal therapy based on estrogen and vaginal progesterone results in the significant improvement of quality of life, elimination of menopausal symptoms and favorable changes of the blood lipids profile. Micronized progesterone does not adversely affect glucose metabolism and blood pressure. Progesterone seems to be safer for the breast as compared with other progestagens. The most recently published results indicate that MHT based on vaginal MP and transdermal estradiol constitutes the safest option of such therapy.